Greener, safer, and stronger: plasma ion-exchanged pharmaceutical glass vials for precision drug delivery dosing - Ahmed Gamal Abd-Elsatar; Hamada Elsayed; Onat Basak; Kamalan Mosas; Aleksandra Nowicka; Hana Kaňková; Akansha Mehta; Jozef Rahel; Jozef Kraxner; Dušan Galusek; Enrico Bernardo (Applied Surface Science Advances)
This study introduces the groundbreaking synergistic influence of plasma and ion-exchange treatment (P-IET), conducted under varying conditions at temperatures of 450 °C and 500 °C for 2, 12, and 24 h, preceded by a few seconds of pre-plasma treatment using a mixed air-argon gas approach. P-IET is a cost-effective, innovative, long-lasting, and industrially scalable process designed to improve the performance of Type I borosilicate glass across various pharmaceutical packaging forms and structures. This treatment produces a durable hydrophilic surface, as confirmed by FTIR analysis, which shows a broad and intense OH group peak at ∼3350 cm⁻¹, along with significant structural changes demonstrating enhanced water-attractive properties. Furthermore, P-IET significantly lowers water contact angles on the glass's inner surface, amplifying its hydrophilicity. These improvements are crucial for water-based drug formulations, facilitating efficient and waste-free drug delivery by enabling complete withdrawal and precise dosing—critical features and requirements for contemporary and modern pharmaceutical applications. This level of performance is crucial for ensuring safety and reducing waste associated with expensive and highly sensitive medications, including cytotoxic therapies and anticancer treatments.Beyond hydrophilicity, P-IET also significantly enhances the mechanical strength of glass by generating a robust compressive layer, hence doubling its resistance to crushing loads by 2124 ± 21 N (e.g., at 500 °C for 24 h) compared to untreated standard vials available on the market today, which have a resistance 1157 ± 91 N. Moreover, P-IET sterilizes the glass surface by removing biological contaminants, microorganisms, and organic residues and improves chemical durability by reducing Na and K ion leach-out, thus assuring long-term chemical stability under various pH conditions. Notably, these are achieved without changing the colour or transparency of the glass vials with preserving their aesthetic or functional integrities. The proposed transformative technology addresses critical challenges in pharmaceutical packaging by introducing a greener, safer, and highly effective solution. P-IET enables the complete withdrawal of medications with precise dosing and boasts exceptional mechanical and chemical resistance. This innovation sets new standards and benchmarks for Type I borosilicate glass while promoting the development of novel drug delivery systems distinguished by their unique reliability and sustainability.